Strategi Tiongkok dalam Membendung Pengaruh Amerika Serikat di Kawasan Pasifik Selatan - Mohammad Arih Muwaffaq; Syasya, Yuania Fadila Mas’udi (Indonesian Journal of Global Discourse, 2025)
This research aims to analyze the strategies that China has used to shift the dominance of the United States in the South Pacific region. This research examines that China uses the Belt Road Initiative strategy and also Chequebook Diplomacy as a strategy to stem the influence of the United States in the South Pacific region. The reason for this is because the Pacific region itself is considered a strategic area for global security. In addition, the South Pacific region is also considered an area that has abundant natural resources. This study uses a qualitative descriptive method. This paper uses the Balance of Power theoretical framework, where countries will balance power to fight against the dominance of a country. In short, in this study the country that dominates the South Pacific region is the United States, so there is a desire for China to stem the dominance of US power. The conclusion of this research analysis is that China is slowly shifting the dominance of the United States and its allies in the South Pacific region, as evidenced by the good response from the assistance provided by China and China's cooperation with countries in the South Pacific region